2020
DOI: 10.3390/insects11090605
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Trehalose-6-Phosphate Synthase Gene Using RNA Interference Inhibits Synthesis of Trehalose and Increases Lethality Rate in Asian Citrus Psyllid, Diaphorina citri (Hemiptera: Psyllidae)

Abstract: Diaphorina citri Kuwayama is the vector of citrus “huanglongbing”, a citrus disease which poses a significant threat to the global citrus industry. Trehalose-6-phosphate synthase (TPS) plays an important role in the regulation of trehalose levels of insects, while its functions in D. citri are unclear. In this study, full-length cDNA sequences of the TPS gene from D. citri (DcTPS) were cloned and its expression patterns at various developmental stages were investigated. The results indicated that DcTPS mRNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The transformant method involves the generation of a transgenic plant (genetically modified organism, GMO) harboring a construct to produce dsRNA targeting the insect mRNA. Meanwhile, the non-transformant delivery methods are GMO-free and include micro-injection of dsRNA directly into the hemolymph [37], topical application on insect body [38,39], soaking insects into a dsRNA solution [40,41], feeding insects with artificial diets containing dsRNA molecules [42][43][44], and feeding insect with plants treated with a dsRNA solution through drenching or trunk injection [45]. Despite the introduction of several dsRNA molecules, however, only those delivery methods that result in insect topical absorption and/or acquisition via feeding are applicable for ACP management in citrus orchards (Table 1).…”
Section: Dsrna Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The transformant method involves the generation of a transgenic plant (genetically modified organism, GMO) harboring a construct to produce dsRNA targeting the insect mRNA. Meanwhile, the non-transformant delivery methods are GMO-free and include micro-injection of dsRNA directly into the hemolymph [37], topical application on insect body [38,39], soaking insects into a dsRNA solution [40,41], feeding insects with artificial diets containing dsRNA molecules [42][43][44], and feeding insect with plants treated with a dsRNA solution through drenching or trunk injection [45]. Despite the introduction of several dsRNA molecules, however, only those delivery methods that result in insect topical absorption and/or acquisition via feeding are applicable for ACP management in citrus orchards (Table 1).…”
Section: Dsrna Deliverymentioning
confidence: 99%
“…RNAi-mediated ACP control has also been tested using feeding assays. Through the ingestion of an artificial diet, several genes including cathepsin D, chitin synthase, inhibitor of apoptosis [55], boule [42], trehalose-6-phosphate synthase [43], and odorant-binding 7 [44], in ACP were silences, leading to a lethal phenotype and/or an abnormal behavioral response. Furthermore, knockdown of the arginine kinase and superoxide dismutase genes through feeding and iPS reduced the ACP adult survival rate [26].…”
Section: Acp Control Using Rnai Technologymentioning
confidence: 99%
“…Soluble Trehalase-Research has shown that Trehalase has critical functions in hemipteran development and survival [142,[155][156][157]. When Trehalase is suppressed then the synthesis of Trehalose is reduced and there is an increase in psyllid mortality [112], with similar reports in planthoppers [158] and other invertebrates [159,160]. Trehalose is the main blood sugar of insects, and the enzyme trehalase is involved in energy metabolism and regulates trehalose levels in cells.…”
Section: Soluble Trehalasementioning
confidence: 84%
“…The earliest RNAi in the Asian citrus psyllid and the glassy-winged sharpshooter sequenced the Arginine kinase , to produce AK- dsRNA’s that were evaluated between species showing RNAi specificity [ 107 ], following studies validated the effects of AK, actin, SOD, Trehalase and cactin -dsRNA’s [ 34 , 50 , 87 , 108 , 109 , 110 , 111 ]. A partial list of genes targeted in other RNAi studies in psyllid have reported knockdown of: trehalase and trehalose-6-phosphate synthase gene [ 112 ]; Superoxide dismutase [ 113 ]; the abnormal normal wing disc gene [ 114 ]; injection and feeding of CYP-dsRNA’s to suppress insecticide resistance [ 115 , 116 ]; suppression of two glutathione S-transferase genes, DcGSTe2 and DcGSTd1, increased psyllid susceptibility to pesticides [ 117 ]; and carboxylesterases to increase nymph mortality [ 118 ]. The strong RNAi response to dsRNA triggers shows that RNAi has the potential to be used to manage psyllid pests.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying that trehalose increases in the ovary after a blood meal is the first indication that its synthesis by the fat body may be necessary for the accumulation of carbohydrates by the ovaries during this rapid developmental phase of the oocytes, i.e., vitellogenesis ( Valle, 1993 ; Roy et al, 2018 ). TPS has previously been detected and/or quantified in fat bodies of several species ( Cui and Xia, 2009 ; Xu et al, 2009 ; Chen et al, 2010 ; Tang et al, 2010 , 2018 ; Xiong et al, 2019 ; Liu et al, 2020 ) including R. prolixus females, where a transcriptome analysis reveals an up-regulation of this enzyme in the fat body of fed females ( Leyria et al, 2020b ). Interestingly, in R. prolixus , the concentration of trehalose in the fat body and hemolymph is lower than that found in other non-hematophagous species ( Oda et al, 2000 ; Singtripop et al, 2002 ; Moriwaki et al, 2003 ; Michitsch and Steele, 2008 ; Huang et al, 2012 ; Kim and Hong, 2015 ; Kh and Keshan, 2019 ) and, more importantly, it is also lower compared to that found in R. prolixus males ( Mariano et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%